Conformational polymorphism, stability and aggregation in spider dragline silk proteins - Dicko, C; Knight, D; Kenney, J; Vollrath, F (Elsevier, 2005)
Spider silk is spun in a complex and unique process, thought to depend on a hydriphobic conversion of a predominantly disordered to a β-sheet rich protein structures. To test this hypothesis we monitored the effect of cationic (DOTAC) and anionic (alkyl sulfate) detergents and of (ii) solvent polarity using a series of alcohols on the secondary structure transition in dilute solutions of native spidroin. Our results showed that the detergents hydrophilic head charge and hydrophobic tail length cooperatively induced either a transition to the β-sheet rich form or a stable helical state. Changing the solvent polarity showed that HFIP and TFE induced formation of stable helical forms whereas MeOH, EtOH and IsoP induced a kinetically driven formulation of β-sheet rich structure.